Penegakan Hukum terhadap Tindak Pidana Penjualan Obat Kadaluwarsa Ditinjau dari Perspektif Hukum Positif di Indonesia - Veni Rosalina (Jurnal Hukum Lex Generalis, 2021)
The regulation, enforcement, and crack down on criminal acts in Indonesia covers almost all areas of human and society life, one of which is in the field of health. In the field of health, especially the sale of pharmaceutical preparations in the form of expired drugs were also targeted by the crimes of rogue people. In fact, this field can be said to be a very vital field and concerns people's life because if the drug is not consumed in accordance with the accurate dose can be toxic to the body. Moreover, if the drug has expired or exceeded the Expired Date (ED) by changing the label of the drug with a new packaging and a new expiry date. People's health and life are not trivial. Therefore, there is a need for strict law enforcement and no tolerance to the perpetrators of the sale of expired drugs in order to cause a deterrent effect for the person and stop the act repeated, especially by other expired drug dealers. Enforcement of the criminal sale of this expired drug has been normatively regulated in positive laws in Indonesia. These arrangements can be found in Health Law and Consumer Protection Law. Both laws are the basis for the enforcement of the law against the criminal sale of expired drugs. The regulation of expired drug distribution crimes is important to accommodate its regulation in positive law in Indonesia especially because considering health is the main capital and has an important role in the framework of growth and life of the Indonesian nation.